A systematic literature review on determinants and outcomes of ESG performance in family firms - Ramona Waldau (Management Review Quarterly, 2024)
Abstract As the predominant business type, family firms hold a unique position to influence the global sector's ESG footprint. However, research on their ESG activities and performance is complex, multi-layered, and currently lacks integration. This review aims to bridge these research disciplines by providing an integrative overview of the current state of family firm ESG literature. By systematically reviewing 127 peer-reviewed studies published between 2000 and mid-2024, I examine the determinants and outcomes of family firm ESG performance, synthesize existing knowledge, and suggest future research directions. The findings reveal the nuanced and at times ambiguous role of family involvement across different ESG dimensions. Additionally, methodological challenges have contributed to inconclusive results in certain areas. This literature review identifies several promising new directions for future research at the intersection of family firm and ESG research to enhance our understanding and foster a more integrated and comprehensive approach to studying ESG in family firms.
Additional information: M14;G32
Keywords: 330; Family firms; Family ownership; ESG; CSR; Literature review; Determinants and outcomes